Liveability, sense of place and behavioural intentions: An exploratory investigation of the Dubai urban area. Issue 1 (5th March 2018) - Tournois, Laurent
Abstract : Purpose: Cities from developing countries strive to compete on a global scale and hence try to attract and retain their residents in offering higher liveability. The purpose of this study is to examine the extent to which liveability influences resident's sense of place and determines residents' behavioural intentions. Design/methodology/approach: A survey was carried out to test the hypotheses using a sample of 362 residents from the city of Dubai (United Arab Emirates). Structural equation modelling and the method suggested by Hayes and Preacher (2010) for mediation analysis were used. Findings: Findings show that residents' preferences for different types of liveability attributes (included in seven dimensions) influence their sense of place that in return shapes their behavioural intentions towards their place of residence. Results also reveal the importance of non-economic attributes of the urban environment. Moreover, residents' sense of place mediates the relationship between liveability and residents' behavioural intentions. Research limitations/implications: Future research could more deeply investigate the social functioning of a place and particularly the role of place identity, as it is recognized to affect residents' attitudes and behaviours. In addition, further developments may contribute to the ongoing debate on the relationship between liveability and growth. Practical implications: From a public policy standpoint, this study suggests that local authorities need to identify a distinct set of economic and non-economic characteristics that will encourage residents to stay longer in the place they live. As such, enhancing liveability represents a critical strategic initiative for cities from developing countries to make them a great place to live. Originality/value: Compared to developed countries' cities, few attempts have been made to investigate the attitudes of residents towards a place and the role of liveability in the context of emerging countries fast-growing urban areas. In addition, findings revealed the importance of place-based meanings, i.e. sense of place, which played a pivotal role in the development of place-protective behaviours.